Caged Emotions: Adaptation, Control and Solitude in Prison - Laws, Ben (Palgrave Studies in Prisons and Penology, 2022)
Introduction -- Chapter 1 – Emotions before prison -- Chapter 2 – Implosions: Suppressing, bottling, trapping emotions -- Chapter 3 – Explosions: anger, rage, and violence -- Chapter 4 – Havens of calm: joy, peace, serenity -- Chapter 5 – The Case for Solitude -- Chapter 6 – When all the options are bad -- Chapter 7 – Emotions and Prison Sociology.